The higher intelligence of the ‘creative minority’ provides the infrastructure for entrepreneurial innovation - Burhan, Nik Ahmad Sufian; Che Razak, Razli; Salleh, Fauzilah; Tovar, Maria Elena Labastida (Elsevier, 2017)
Does the intelligence quotient (IQ) in a nation regulate the ease of doing business? Based on the normal distribution of IQ scores within a nation, the population was classified into three groups, specifically intellectual class, average ability, and non-intellectual class, which were represented by the 95th, 50th, and the 5th percentiles of IQ level respectively. Using a robust regression method, the impact of each IQ class on the ease of doing business (EDB) index was examined. The sub-indicators of the ten business regulatory environment across 71 countries were studied. In this study, the effect of IQ was controlled for the levels of economic freedom, GDP per capita, freedom of corruption, and tertiary education. Results revealed strong evidence that the IQ of the intellectual class had contributed most to the enhancement of the regulatory environment, which is supportive for entrepreneurship. This result was consistent with the term ‘creative minority’ coined by the prominent historian Arnold Toynbee. It was concluded that the IQ of the people from the intellectual class is the most significant factor for creating a business regulatory environment that eases the entrepreneurs. This occurs through their competent and virtuous leadership that enhances the quality and efficiency of institutions across countries.